Probiotic bacteria grown with chestnut honey enhance in vitro cytotoxicity on breast and colon cancer cells - Celebioglu, Hasan Ufuk (Archives of Biological Sciences, 2020)
Paper description: Probiotics can exert health benefits and with other food constituents their health effects can be improved. This study investigated the effects of chestnut honey on probiotic bacteria, and the in vitro cytotoxic effects on breast and colon cancer cells. Auto-aggregation and surface hydrophobicity tests for Lactobacillus acidophilus LA-5 and Lactobacillus rhamnosus GG were performed, and viabilities of MCF-7 and Caco-2 cells were examined by the MTT assay. Chestnut honey positively modulated the probiotic properties. Probiotics grown on honey exhibited cytotoxic effects on breast and colon cancer cells. Combinations of honey and probiotics have the potential to formulate new nutraceuticals. Abstract: Chestnut honey has been used as ethnomedicine. Probiotics are defined as live microorganisms that can provide a health benefit, impeding the development of several health conditions and diseases, including cancer. This study aims to investigate the effects of chestnut honey on probiotic bacteria and the in vitro cytotoxic effects of the combination of probiotics and chestnut honey on cancer cells. First, the effects of chestnut honey on the growth of bacteria were examined, followed by its effects on the probiotic properties of Lactobacillus acidophilus LA-5 and Lactobacillus rhamnosus GG. Once the bacteria had grown on chestnut honey, the in vitro cytotoxic effects on breast and colon cancer cell lines, MCF-7 and Caco-2, respectively, and a non-cancerous breast epithelial cell line, MCF-10A, were investigated. Chestnut honey positively affected the probiotic bacteria by increasing the growth and modulating probiotic properties such as autoaggregation and surface hydrophobicity. Furthermore, probiotics grown on chestnut honey had more cytotoxic effects on the cancer cell lines than probiotics or honey alone. The present study showed that new combinations of honey and probiotics have the potential to formulate new nutraceuticals. https://doi.org/10.2298/ABS200114027C Received: June 14, 2020; Revised: June 19, 2020; Accepted: June 20, 2020; Published online: June 23, 2020 How to cite this article: Celebioglu HU. Probiotic bacteria grown with chestnut honey enhance in vitro cytotoxicity on breast and colon cancer cells. Arch Biol Sci. 2020;72(3):329-38.